2020
DOI: 10.1088/2053-1591/ab66aa
|View full text |Cite
|
Sign up to set email alerts
|

High cycle fatigue behavior of a dissimilar metal welded joint in ultra-supercritical steam turbine rotor

Abstract: The high cycle fatigue (HCF) property and microstructure of a dissimilar metal welded joint (DMWJ) for ultra-supercritical steam turbine rotor were systematically investigated in this paper. The DMWJ was fabricated using narrow gap submerged arc welding (NG-SAW) technique with buttering layer. Conditional fatigue strength of 30Cr1Mo1V (BM-1), buttering layer (BL), weld metal (WM) and 30Cr2Ni4MoV (BM-2) based on S-N curve was obtained by HCF tests at room temperature. The microstructure and second-phase carbide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…For multi-layer and multi-pass weld, the toughness of interlayer heat affected zone is most sensitive to cooling rate. Wang et al 18,19) studied the micro-zone properties of dissimilar steel welded rotor joints (30Cr1Mo1V/30Cr2Ni4MoV) with transition layer, and found that the local mechanical properties of the joints were uneven, showing gradient distribution in the heat affected zone.…”
Section: Introductionmentioning
confidence: 99%
“…For multi-layer and multi-pass weld, the toughness of interlayer heat affected zone is most sensitive to cooling rate. Wang et al 18,19) studied the micro-zone properties of dissimilar steel welded rotor joints (30Cr1Mo1V/30Cr2Ni4MoV) with transition layer, and found that the local mechanical properties of the joints were uneven, showing gradient distribution in the heat affected zone.…”
Section: Introductionmentioning
confidence: 99%